3-Methyl-1-{(E)-[1-(4-methylpyridin-2-yl)ethylidene]amino}thiourea: crystal structure and Hirshfeld surface analysis - Lai, Lee Chin; Che Nursarah Che AbdulRahman,; M. Ibrahim M.Tahir,; Ravoof, Thahira Begum S. A.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (2018)
The title disubstituted thiourea derivative, C10H14N4S, features an almost planar imine (E configuration, C3N) core flanked by thiourea (CN2S) and methylpyridyl (C5N) residues (each plane has a r.m.s. deviation of the respective fitted atoms of 0.0066 A ° ). The dihedral angles between the core and the thiourea and pyridyl residues are 20.25 (8) and 7.60 (9)⁰, respectively, indicating twists in the molecule; the dihedral angle between the outer planes is 13.62 (7)⁰. There is an anti-disposition of the amine-N—H atoms which allows for the formation of an intramolecular amine-N—H...N(imine) hydrogen bond that closes an S(5) loop. In the crystal, amine-N—H...N(pyridyl) hydrogen bonds lead to zigzag (glide symmetry) supramolecular chains along the c-axis direction. These are connected into a supramolecular layer propagating in the bc plane by thioamide- N—H...S(thione) hydrogen bonds via eight-membered thioamide {...HNCS}2 synthons.